A case study of IT implementation in public university: its barriers and challenges - Setiawan, I Made Agus (Jurnal Ilmu Komputer; Vol 5 No 2: September 2012, 2012)
This paper attempts to study the IT implementation in public sector organizations particularly highereducation institution in developing countries. The goal is to understand the aspects that could hamperthe successful IT implementation process in educational institution. An interpretive case study with 2weeks empirical data collection has been performed in public university in Indonesia. This studyfound several factors that hamper the implementation process in the university, either from internal orexternal organization, including limited human resources, lack of management commitment, lack ofclear job description among staffs, lack of appropriate planning and strategy for systems developmentand implementation, ineffective communication & coordination, lack of funds, lack of rewards, andgovernment policies. These findings are tie in well with the barriers and challenges found in theliterature.
Keywords: IT Implementation; IT adoption; Higher Education Institution; Developing Countries